Integrated Transcriptomic and Epigenetic Study of PCOS: Impact of Map3k1 and Map1lc3a Promoter Methylation on Autophagy - Qin, Yulan; Li, Ting; Zhao, Hui; Mao, Zhanrui; Ding, Chunxia; Kang, Yani (Frontiers in Genetics, 2021)
Polycystic ovary syndrome (PCOS) is a prevalent heterogeneous endocrine and metabolic disorder in women of reproductive age. Epigenetic mechanisms contribute to the development of PCOS. Nevertheless, the role of DNA methylation in the development of PCOS remains unclear. To investigate the molecular mechanisms underlying the hyperandrogenic phenotype of PCOS, dihydrotestosterone (DHT)-induced prenatally androgenized (PNA) mice were used to mimic this phenotype. Ovarian samples from PNA and control mice were subjected to methyl-CpG-binding domain (MBD)-seq and RNA-seq, and validation was conducted using methylation-specific polymerase chain reaction (MSP) and RT-qPCR. Immunohistochemical analysis (using anti-LC3II antibody) and transmission electron microscopy were conducted using ovarian tissue sections (which included granulosa cells) from PNA and control mice. There were 857 genes with differentially methylated promoter regions and 3317 differentially expressed genes (DEGs) in the PNA mice compared to the control mice. Downregulation of Dnmt1 (which encodes DNA methyltransferase 1), accompanied by global hypomethylation, was observed in the PNA mice compared to the control mice. The promoter regions of Map3k1 (which encodes MEKK1) and Map1lc3a (which encodes LC3II) were hypomethylated, accompanied by upregulation of Map3k1 and Map1lc3a mRNA expression. The autophagy profiling results showed that LC3II protein expression and autophagosomes were significantly increased in the granulosa cells of PNA mice. Additionally, the mRNA expression of genes related to the mitogen-activated protein kinase (MAPK)/p53 pathway (Mapk14, Mapkapk3, and Trp53) and the autophagy-related gene Becn1 were significantly increased. DHT could change the DNA methylation and transcription level of Map3k1 and lead to an activation of autophagy in granulosa cells. These observations indicated that the change in autophagy may be driven by MAPK/p53 pathway activation, which may have been caused by DHT-induced transcriptional and methylation level changed of the key upstream gene Map3k1. Our study provides a novel genetic basis and new insights regarding the pathogenesis of PCOS.